Convergence Rate of the Truncated Euler-Maruyama Method for Neutral Stochastic Differential Delay Equations with Markovian Switching (Journal of Computational Mathematics, 2021)
The key aim of this paper is to show the strong convergence of the truncated Euler-Maruyama method for neutral stochastic differential delay equations (NSDDEs) withMarkovian switching (MS) without the linear growth condition. We present the truncated Euler-Maruyama method of NSDDEs-MS and consider its moment boundedness underthe local Lipschitz condition plus Khasminskii-type condition. We also study its strongconvergence rates at time $T$ and over a finite interval $[0, T]$. Some numerical examples aregiven to illustrate the theoretical results.